Determinant of Customers' Revisit Intention: Study of MSMEs in Indonesia - Abdullah Syakur Novianto; Sudarmiatin Sudarmiatin; Agus Hermawan (Cita konsultindo, 2023)
MSMEs have an essential role in the economy of Indonesia. MSMEs can absorb around 97% of the national workforce compared to large businesses, which absorb only 3%. A coffee shop is one of the MSMEs that has proven to survive during the Covid-19 pandemic. The ANT shop is an MSME located in Probolinggo City and has a unique place and natural atmosphere. This study examines the effect of price value and taste values on revisit intention through memorable experiences as variable mediation in MSMEs in Indonesia. Primary data was obtained with a spread questionnaire to visitors who come to Kedai ANT. Partial least squares–structural equation modeling used to test the effect of price value and taste value on revisit intention through memorable experience as variable mediation. The results of this study are price value found no direct influence against ME and no direct influence towards revisit intention. In contrast, the taste value is found to be directly influential to memorable experiences and not directly impactful to revisit intention.